2004
DOI: 10.1111/j.1365-2249.2004.02616.x
|View full text |Cite
|
Sign up to set email alerts
|

Mannan-binding lectin modulates the response to HSV-2 infection

Abstract: SUMMARYViruses have developed numerous strategies to escape recognition by the immune system. However, some viruses such as herpes simplex virus-2 (HSV-2) are recognized by initiators of the complement system, e.g. mannan-binding lectin (MBL). To study the effects of MBL deficiency during viral infection we have chosen a model of generalized HSV-2 infection. We infected MBL-A and MBL-C double knockout mice (DKO) with HSV-2 via the intraperitoneal (i.p.) route. DKO mice cleared HSV-2 from the liver less efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
66
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 46 publications
2
66
0
1
Order By: Relevance
“…Other patient populations did not show such a relationship (56 -58) and thus it appears that the effect of MBL deficiency is revealed only under certain clinical conditions. In our studies aimed at clarifying the role of MBL, we have found that MBL null mice are susceptible to infection with S. aureus (24) and HSV-2 (25). The present study adds P. aeruginosa to the list of pathogens that show increased infectivity in MBL-deficient animals.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Other patient populations did not show such a relationship (56 -58) and thus it appears that the effect of MBL deficiency is revealed only under certain clinical conditions. In our studies aimed at clarifying the role of MBL, we have found that MBL null mice are susceptible to infection with S. aureus (24) and HSV-2 (25). The present study adds P. aeruginosa to the list of pathogens that show increased infectivity in MBL-deficient animals.…”
Section: Discussionmentioning
confidence: 89%
“…We postulated that MBL, a serum protein, might play a key role as an innate immune molecule able to limit the systemic spread of locally infecting pathogens in burned tissue. This idea was informed by the knowledge that MBL is deployed quickly to sites of infection as has been shown in the lung (23) in addition to our previous work demonstrating that MBL null mice are highly susceptible to infection with Staphylococcus aureus (24) and HSV-2 (25).…”
mentioning
confidence: 99%
“…This was proposed by Kruse et al (131), who demonstrated that patients with MBL levels <100 ng/mL had a higher abortion rate. Some urogenital infections such as vulvovaginitis, herpes simplex virus-2 infection, vulvovaginal candidiasis and vestibulitis appear to be linked to low MBL levels in comparison to healthy controls (132)(133)(134). Downstream complement deficiencies are typically associated with recurrent invasive infections of Neisseria meningitidis and gonorrhea (135).…”
Section: Infectionsmentioning
confidence: 99%
“…Furthermore, promoter polymorphisms in the MBL2 gene (X and Y) influence the level of functional MBL (18). MBL-deficient individuals are more susceptible to a range of infections, especially in early infancy before the maturation of the adaptive immune system (14), and MBL is known to modulate the response to viral infections, including herpesviruses (3,4,23). Thus, MBL increases neutralization of herpes simplex virus type 2 (HSV-2), MBL deficiency is more prevalent in symptomatic HSV-2 patients (4), and MBL-deficient individuals are at greater risk of recurrent HSV-2 infection (23).…”
mentioning
confidence: 99%